Pengaruh Metode Pembelajaran Active Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak (Penelitian di Kelas VIII MTs Ponpes Cipari, Garut) - Maulid, Andre Achmad; Nasrullah, Yufi; Saifullah, Iman (Jurnal Pendidikan Agama Islam, 2024)
The background to this research is the lack of learning innovation used by teachers in learning activities and the lack of students' ability to achieve maximum results. One of these things is influenced by learning activities where some students are bored with these learning activities, the less than optimal use of learning methods is influenced by several factors, namely, there are students who are less active and enthusiastic in the learning process, one of the causes is that the learning methods applied are less varied so that it seemed monotonous and still classical in nature using question and answer methods and lectures. Therefore, researchers were inspired to conduct research at this school. The purpose of this research is to find out (1) how Active Learning Learning Methods are used at Mts Ponpes Cipari Garut, (2) what are the student learning outcomes at MTs Ponpes Cipari Garut, and (3) what is the influence of Active Learning Learning Methods on Student Learning Outcomes in Moral Creed Subjects at Mts Ponpes Garut. The method used in this research is a quantitative method with descriptive survey analysis techniques, namely research that is based on phenomena that occur by making decisions from sample data using statistical tests. By describing or illustrating phenomena. In this study, a population of 28 respondents was used with a sample using the Nonprobability Sampling technique of 28 respondents. The results obtained include (1) there is an influence of active learning methods at Mts Ponpes Cipari Garut with an average percentage score of 77.4% in the Good category. (2) The student learning outcomes at Mts Ponpes Cipari Garut with an average percentage score of 80.1% are in the Good category. (3) The influence of active learning methods on student learning outcomes in the Moral Creed subject at Mts Ponpes Cipari Garut with the results of t count > t table (6.71 > 2.06) This means that H1 is accepted and H0 is rejected. With a percentage result of 64.41% while 36.58% is influenced by other factors such as the environment where students live, parental support as well as guidance from competent teachers.